Maize and soybean meal supplementation improves utilization of low-quality forage in lambs drinking high-sulfate water - Wolf Celone, Ursula Ingrid (2025)
Context. Supplementation of low-quality forage with maize and soybean meal (SBM) has been widely studied as a strategy to improve forage intake and nutritional status. However, the effects of maize and SBM supplementation in ruminants consuming high sulfate-containing water remain uninvestigated. Aim. The objective of this study was to assess the effects of maize and SBM supplementation on utilization of low-quality (CP: 5.3%; NDF: 81.9%) forage, nitrogen balance, and ruminal hydrogen sulfide (H2S) production in lambs drinking high-sulfate water (7947 mg/L of total dissolved salts; 4430 mg/L of sulfate). Methods. Eighteen Hampshire Down lambs were utilized in a six-treatment × two period experiment. The treatment structure was a 2 × 3 factorial, with two levels of SBM (0% and 0.75% of liveweight (LW)) and three levels of maize (0%, 0.5%, and 1.0% of LW). Key results. Water intake, total organic matter (OM) and total digestible OM intake increased with both SBM (P < 0.01) and maize supplementation (P < 0.05). Soybean meal and maize supplementation enhanced N balance and N-use efficiency (P < 0.01). Maize tended to reduce ruminal H2S gas production at the 0.75% SBM supplementation, whereas maize increased H2S production when SBM was not supplemented. Conclusions. Supplementing low-quality forage with maize and SBM improved forage intake and N utilization in lambs consuming high-sulfate water, without increasing ruminal H2S gas production. Implications. Maize and SBM can serve as effective supplements for improving animal performance when feeding low-quality forage in environments with high-sulfate drinking water.